The Local Political Policies: The Dynamics of the Political Party Coalition in the Election Contestation of the Governor West Nusa Tenggara Province Indonesia - Winengan (International Journal of Criminology and Sociology, 2022)
This paper analyzed political party coalitions in the 2018 West Nusa Tenggara Provincial Governor election. Research methods included in-depth interviews, observations, and review of documents. Analysis of data and information identified choice of political party coalition originated from distribution of political office positions and potential victory of political parties as two major factors in decision making. Analysis revealed in regional election contests consideration in choosing a political party coalition partner prioritizes pragmatic interest rather than the similarity of political party ideology.